PENGARUH FAKTOR LINGKUNGAN TERHADAP MUTU DAUN DAN DINAMIKA HARGA TEMBAKAU MADURA TAHUN 2021–2025 - Rina Susanti; Rayyan Muhammad; Matsayni Matsayni (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2026)
Fluctuations in tobacco quality and price represent a major challenge in local tobacco agribusiness, particularly in regions where production is highly sensitive to environmental variability such as Madura, Indonesia. Variations in agroclimatic conditions can influence the chemical characteristics of tobacco leaves, which in turn affect grading and price formation at the farmer level. This study aims to examine the effects of environmental factors on tobacco leaf quality and to analyze their implications for the price dynamics of Madura tobacco during the 2020–2025 observation period. The research employs a quantitative approach using a field case study involving 30 tobacco farmers in Pamekasan Regency. Environmental variables include rainfall and harvest temperature, while leaf quality is measured using three indicators: moisture content, nicotine content, and reducing sugar. Data are analyzed using descriptive statistics, trend analysis, and multiple linear regression models to estimate the influence of environmental factors on leaf quality and the effect of quality on tobacco prices. The results show that rainfall and harvest temperature significantly affect leaf quality indicators (p < 0.05). Higher rainfall increases leaf moisture content (? = +0.42) and decreases nicotine (? = ?0.38) and reducing sugar (? = ?0.31), while higher harvest temperature decreases moisture content (? = ?0.29) and increases nicotine (? = +0.41) and reducing sugar (? = +0.35). Furthermore, leaf quality significantly influences tobacco prices at the farmer level, with nicotine showing the strongest positive effect (? = +0.52; p = 0.001), while moisture content has a negative effect (? = ?0.36; p = 0.012). Quality variations explain approximately 67% of price variation (R² = 0.67). These findings indicate that environmental variability affects tobacco prices indirectly through changes in leaf quality. The study contributes to the agribusiness literature by empirically demonstrating the environment–quality–price linkage in smallholder tobacco production systems and provides an analytical basis for improving tobacco competitiveness through environmental adaptation, postharvest quality management, and greater transparency in grading systems.